Developing a built-in definition of fraction manipulative to enhance students’ conceptual understanding - Darmawijoyo; Yukans, Septy Sari; Kurniadi, Elika; Pratiwi, Weni Dwi (Jurnal Elemen, 2026)
This study addresses the challenge of students limited conceptual understanding of fractions by developing a physical manipulative called the Built-in Definition of Fraction (BDF). Using design research developmental studies, data were collected through written tests, questionnaires, and interviews. A total of 41 fifth-grade students participated in the study. The BDF and its accompanying student worksheet integrate dual visual-symbolic representations, that link each concrete action to its corresponding fraction notation and scaffold students in constructing their own understanding of fractions, offering a new approach to using fraction manipulatives. Validation results show that the manipulative is valid, practical, and effective in supporting student understanding of basic fraction concepts, equivalent fractions, and same-denominator addition, even with minimal teacher guidance. Student performance was high across visual-concrete tasks. However, a noticeable gap emerged in unlike-denominator addition between visual concrete performance (88%) and formal-symbolic procedures (77%). This finding highlights the need for additional scaffolding to help students transition more smoothly from concrete representations to abstract symbolic reasoning.